2010 IEEE Sensors 2010
DOI: 10.1109/icsens.2010.5690450
|View full text |Cite
|
Sign up to set email alerts
|

A tactile proximity sensor

Abstract: This paper introduces a novel tactile sensor with the ability to detect objects in the sensor's near proximity. For both tasks, the same capacitive sensing principle is used. The tactile part of the sensor provides a tactile sensor array enabling the sensor to gather pressure profiles of the mechanical contact area. Several tactile sensors have been developed in the past. These sensors lack the capability of detecting objects in their near proximity before a mechanical contact occurs. Therefore, we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…principle was developed in a previous work [1]. Sensor identification for the tactile mode and further sensor designs where presented in [2].…”
Section: Introductionmentioning
confidence: 99%
“…principle was developed in a previous work [1]. Sensor identification for the tactile mode and further sensor designs where presented in [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, acceleration sensors, optical proximity sensors and temperature sensors have been used. In [12] we have already introduced a prototype tactile proximity sensor, so only the necessary basics of this sensor will be explained here. Further details can be obtained in this publication.…”
Section: Introductionmentioning
confidence: 99%
“…MODELLING THE TACTILE PARTAs explained in[12], the behaviour of the tactile sensor is mainly based on the electrical behaviour of a capacitor and the mechanical behaviour of the used polymer foam between the capacitor plates. Applying a load CJp on this tactile Capacitance of a polymer foam filled taxel sensor leads to a compression of the foam which changes the geometry of the air filled capacitor.…”
mentioning
confidence: 99%
“…In recent years, integrated sensors functioning as both proximity and tactile sensors have been explored as an effort to save cost and space [13][14][15][16]. Göger et al reported a capacitive tactile sensor module that is capable of sensing proximity in combination with another module in the different operational mode [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Göger et al reported a capacitive tactile sensor module that is capable of sensing proximity in combination with another module in the different operational mode [13,14]. They employed a polymer foam between electrode layers as a deformable dielectric to sense the tactile pressure.…”
Section: Introductionmentioning
confidence: 99%